Pengendalian Mutu Produk pada Pabrik Tepung Tapioka di CV Wangun Mandiri - Prasetianah, Tiara; Praya Prameswari, Chao; Hosea, Michael; Nurasyyura Fajrani, Humaira; Kautsar, Altair; Nazhifa Solihin, Zaqia (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to analyze the quality of tapioca flour produced by CV Wangun Mandiri, Bogor. The research employs several quality control tools, including checksheets, Pareto diagrams, and fishbone diagrams. Tapioca flour is a widely demanded raw material, as it is frequently used in various popular Indonesian food products. However, the production process often encounters defects and inconsistencies that reduce overall product quality. This study uses primary data collected through direct interviews and analyzed using a descriptive qualitative approach. The results indicate that the most frequent defect is wet tapioca flour, followed by damaged packaging and improper product color. The fishbone analysis identifies multiple contributing factors categorized into six groups: human, methods, machines, materials, environment, and measurement. The findings imply the need for improvements in standard operating procedures, raw material supervision, and the adequacy of production facilities and infrastructure.